Energy-Saving Effect of Discolored Decorative Boards in Flexible Interior Space - Wenhai, Zeng; Liting, Jiang; Chen, Wang; Xiaoqiang, Yu; Hongbing, Zhou (Journal of landscape research, 2017)
Green,energy conservation and environmental protection have increasingly become the theme of the sustained and healthy development of cities against the background of new urbanization,which indicates that the problem of building energy consumption has received growing attention.This paper explores the impact of energy-saving decorations in flexible interior space on energy-saving effect of buildings so as to broaden the horizon of energy conservation in building,thereby alleviating the problem of energy shortage in China.